The Effect of Learning Model (PJBL & PBL) and Learning Style (Visual & Auditory) on Biology Learning Outcomes - Agsen Hosanty Susana Billik (Quagga: Jurnal Pendidikan dan Biologi, 2025)
This study was conducted to determine the effect of learning models and learning styles on biology learning outcomes on Coordination System material. The problems behind this research are the low learning outcomes of biology (40% of students have not reached the KKM), monotonous learning methods, the diversity of student learning styles that have not been accommodated, the lack of application of innovative learning models, and learning that is still limited to memorization. The research objectives were to determine: (1) differences in biology learning outcomes between students taught with PJBL and PBL models, (2) differences in biology learning outcomes between students with visual and auditory learning styles, and (3) interaction between learning models and learning styles on biology learning outcomes. This study used a quasi-experimental method with a 2 x 2 factorial design. Data analysis used two-way ANOVA at a significant level of 0.05. The results showed that: (1) there is a difference in learning outcomes between students taught with PJBL and PBL models (sig. 0.40 < 0.05), (2) there is no difference in learning outcomes between students with audio and visual learning styles (sig. 0.671 > 0.05), and (3) there is no interaction between learning models and learning styles on biology learning outcomes (sig. 0.766 > 0.05).